Impact of alcohol checks and social norm on driving under the influence of alcohol (DUI). (July 2015) - Meesmann, Uta; Martensen, Heike; Dupont, Emmanuelle
Highlights: We investigated the impact of alcohol checks and social norm on drink-driving. We developed a logistic regression model on two levels: national and individual. The Social norm is positively related to drunk driving on both levels. Countries that conduct more alcohol checks have less drunk driving. Paradoxically, individuals checked for alcohol are more likely to drink-drive. Abstract: This study investigated the influence of alcohol checks and social norm on self-reported driving under the influence of alcohol above the legal limit (DUI). The analysis was based on the responses of 12, 507 car drivers from 19 European countries to the SARTRE-4 survey (2010). The data were analysed by means of a multiple logistic regression-model on two levels: (1) individual and (2) national level. On the individual level the results revealed that driving under the influence (DUI) was positively associated with male gender, young age (17–34), personal experience with alcohol checks, the perceived likelihood of being checked for alcohol, perceived drunk driving behaviour of friends (social norm) and was negatively associated with higher age (55+). On a national level, the results showed a negative association with a lower legal alcohol limit (BAC 0.2 g/l compared with BAC 0.5 g/l) and the percentage of drivers checked for alcohol. DUI was positively associated with the percentage of respondents in the country that reported that their friends drink and drive (social norm). The comparison of the results obtained on national and individual levels shows a paradoxical effect of alcohol checks: Countries with more alcohol checks show lower DUI (negative association) but respondents who have been personally checked for alcohol show a higher chance of DUI (positive association). Possible explanations of this paradox are discussed. The effects of the social norm variable (perceived drunk driving behaviour of friends) are positively associated with DUI on both levels.